Technical Complications during Long-term Subarachnoid or Epidural Administration of Morphine in Terminally Ill Cancer Patients: A Review of 140 Cases. Issue 4 (July 1991) - Crul, Ben J.P.; Delhaas, Elmar M.
Abstract : The type and incidence of technical complications (e.g., obstruction and dislocation of the catheter and infection) in long-term (ten to 366 days) spinal morphine administration in terminally ill cancer patients by means of an epidural or subarachnoid catheter are presented. Total treatment time was 8650 days, of which patients spent 6175 at home. Portable external mini infusion pumps were used with satisfactory results in 15 patients of the epidural group ( n = 110) and in all patients receiving subarachnoid morphine ( n = 30). In the other 95 patients of the epidural group, intermittent bolus injections were used. During the first 20 days of treatment, a significant difference (chi-square test, p = 0.02) in the incidence of complications was observed between the epidural group (8%) and the subarachnoid group (25%). During the remainder of the treatment period the complication rate rose to 55% in patients receiving epidural morphine and declined to 5% in the subarachnoid group, a significant difference (chisquare test, p = 0.001). The most frequent complication in the epidural group was obstruction and dislocation of the catheter, probably due to the development of epidural fibrosis. This problem became apparent in 50% of patients during the treatment period from Day 20 to 366. In patients receiving subarachnoid morphine, the prevalent complication was CSF leakage, which was observed only during the first two weeks of treatment. The subarachnoid route is preferred for patients expected to live longer than one month. For patients with a shorter life expectancy, epidural administration can yield acceptable results.